Supply Chain Analysis and Marketing Efficiency of Robusta Coffee at CV. Kopi Citarasa Persada Tutur District, Pasuruan Regency - Sukur, Anisa Aurelia; Winarno, Sri Tjondro; Fitriana, Nisa Hafi Idhoh (Kadiri University - Faculty of Agriculture, 2024)
The coffee industry plays an important role in Pasuruan Regency, a region in Indonesia known for producing high-quality coffee. The coffee industry in Pasuruan Regency faces several problems affecting its business prospects. One of the main problems faced by coffee farmers is limited market access affecting the sustainability of local economic stability. This study investigates the coffee supply chain flow at CV Kopi Citarasa Persada, a leading coffee company in Pasuruan Regency, Indonesia. The main focus of this study is to identify and analyze the main challenges affecting the efficiency of the robusta coffee supply chain at CV Kopi Citarasa Persada. The research was conducted in 2024 and involved 10 respondents, including company management and farmer group leaders. The variables analyzed included product, information, and financial flows. The analysis method is marketing margin and farmer's share, calculated through consumer and producer prices. This calculation can help increase transparency in the supply chain and allow all stakeholders to make better decisions. Preliminary analysis shows challenges to raw material inventory that can lead to unavailability and disruptions in the production process with complex supply chain structures and significant efficiency potential. In addition, this research also provides a basis for recommendations for improvements in inventory management to address the uncertainty of demand and supply. With the positive goal of making this research a reference for improving the operational efficiency of coffee companies, this study will be used to improve the operational efficiency of coffee companies in Indonesia.